Impostor Syndrome sebagai Prediktor Kecanduan AI: Sebuah Pendekatan Kuantitatif - YULIANI, RAHMA AURA YULIANI; SUKOCO, CEMARA SAMARANTU SUKOCO; SARI, MITA TIANA SARI (Jurnal Ilmiah Penelitian Psikologi, 2025)
The phenomenon of impostor syndrome and AI addiction is increasingly relevant among university students. AI addiction is a state in which a person becomes highly dependent and finds it difficult to break away from the use of artificial intelligence (AI) technology. This study aims to determine the effect of impostor syndrome on AI addiction among college students. The method used is quantitative with data collection techniques through questionnaires on 130 respondents. The measuring instruments used were Impostor Phenomenon Scale and Dependent on Artificial Intelligence Scale, with Cronbach's alpha of 0.876 and 0.761 respectively. The data analysis technique used simple linear regression analysis with the help of SPSS 26 software. The results of the analysis showed a p value = 0.001 <0.05, so there is a significant influence between impostor syndrome and AI addiction. The R square value of 0.076 indicates that impostor syndrome has an effect of 7.6% on AI addiction. So it can be concluded that the hypothesis in this study related to the influence of impostor syndrome on AI addiction among college students can be accepted